Impaired intestinal permeability in patients with multiple sclerosis - Fialová, Lenka; Barilly, Pavla; Štětkářová, Ivana; Bartoš, Aleš; Nosková, Libuše; Zimová, Denisa; Židó, Michal; Hoffmanová, Iva (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2025)
BACKGROUND: A number of recent studies have shown that the intestinal microbiome, part of the brain-gut axis, is implicated in the pathophysiology of multiple sclerosis. An essential part of this axis, is the intestinal barrier and gastrointestinal disorders with intestinal barrier dysregulation appear to be linked to CNS demyelination, and hence involved in the etiopathogenesis of multiple sclerosis (MS). OBJECTIVE: The aim of this study was to evaluate the integrity of the intestinal barrier in patients with clinically definite multiple sclerosis (CDMS) and clinically isolated syndrome (CIS) using two serum biomarkers, claudin-3 (CLDN3), a component of tight epithelial junctions, and intestinal fatty acid binding protein (I-FABP), a cytosolic protein in enterocytes. METHODS: Serum levels of CLDN3 in 37 MS patients and 22 controls, and serum levels of I-FABP in 46 MS patients and 51 controls were measured using commercial ELISA kits. Complete laboratory tests excluded the presence of gluten-related disorders in all subjects. Thirty MS patients received either disease-modifying drugs (DMD), immunosuppression (IS) or corticosteroid treatment. RESULTS: CLDN3 levels were only significantly higher in the MS patients treated with DMD or IS compared to the control group (P=0.006). There were no differences in I-FABP serum levels between the groups. Serum CLDN3 levels did not correlate with serum I-FABP levels in CDMS, in CIS patients or controls. CONCLUSIONS: In multiple sclerosis patients, the intestinal epithelium may be impaired with increased permeability, but without significant enterocyte damage characterized by intracellular protein leakage. Based on our data, CLDN3 serum levels appear to assess intestinal dysfunction in MS patients but mainly in treated ones.
Keywords: claudin-3; Fatty Acid-Binding Proteins; roztroušená skleróza; Middle Aged; mužské pohlaví; studie případů a kontrol; Adult; Intestinal Mucosa; Multiple Sclerosis; ženské pohlaví; Humans; Intestinal Barrier Function; biologické markery; permeabilita; lidé středního věku; střevní sliznice; funkce střevní bariéry; Permeability; Case-Control Studies; dospělí; Biomarkers; proteiny vázající mastné kyseliny; Female; Claudin-3; lidé; Male